System-size dependence of the charged-particle pseudorapidity density at sNN=5.02TeV for pp, p–Pb, and Pb–Pb collisions - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (Elsevier, 2023)
We present the first systematic comparison of the charged-particle pseudorapidity densities for three widely different collision systems, pp, p–Pb, and Pb–Pb, at the top energy of the Large Hadron Collider ( √sNN = 5.02 TeV) measured over a wide pseudorapidity range (−3.5 < η < 5), the widest possible among the four experiments at that facility. The systematic uncertainties are minimised since the measurements are recorded by the same experimental apparatus (ALICE). The distributions for p–Pb and Pb–Pb collisions are determined as a function of the centrality of the collisions, while results from pp collisions are reported for inelastic events with at least one charged particle at midrapidity. The charged-particle pseudorapidity densities are, under simple and robust assumptions, transformed to charged-particle rapidity densities. This allows for the calculation and the presentation of the evolution of the width of the rapidity distributions and of a lower bound on the Bjorken energy density, as a function of the number of participants in all three collision systems. We find a decreasing width of the particle production, and roughly a smooth ten fold increase in the energy density, as the system size grows, which is consistent with a gradually higher dense phase of matter.
Keywords: Pseudorapidity; Physics; Charged particle; Rapidity; Range (aeronautics); Nuclear physics; Particle physics; Hadron; Collider; Ion; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.04